The Comintern and the Communist Parties of South Africa, Canada, and Australia on Questions of Imperialism, Nationality and Race, 1919-1943 - Drachewych, Oleksa (My University, 2017)
In 1919, the Bolshevik Party of Russia formed the Communist International (Comintern) to lead the international communist movement. As part of its efforts, it maintained a strong commitment to supporting colonial liberation, self-determination of nations, and racial equality. Many scholars of the Comintern and the Soviet Union assume that Moscow demanded firm discipline of all member parties and these parties largely followed its lead. But the Comintern was not as monolithic as is often presumed. Colonial affairs frequently were overlooked and European Communist Parties often skirted their commitment to supporting their colonial counterparts. Individual communists took it upon themselves to promote anti-imperialism or racial equality, but their efforts were frequently hampered by the tactical shifts of the Comintern and eventually, the erosion of Moscow’s interest. Frequently, the prioritization of certain issues in the Comintern proved to be the most important factor in determining Comintern interference in member parties. This dissertation includes the first comparative analysis of the Communist Parties of South Africa, Canada and Australia on issues of anti-imperialism, nationality, and race. In comparing these parties, this study explores the limits of Moscow’s control of other Communist Parties, while detailing the similarities and differences in the efforts of these three parties to combat imperialism, support colonial liberation, and fight for national rights and racial equality. This dissertation is the first to detail the Canadian and Australian communism’s efforts, sometimes on their own initiative, on anti-imperialism, nationality and racial equality during the interwar period, to provide new conclusions about Comintern intervention in South Africa, and to highlight the prioritization of the Comintern as each party sees Moscow’s intervention on these issues to very different degrees.
Keywords: Communism; Comintern; Race; Anti-Imperialism; Self-Determination; Soviet Union; Communist Party of Canada; Communist Party of Australia; Communist Party of South Africa